Seismic profiling-based modeling of geometry and sedimentary architecture of the Late Pleistocene delta in the Beibu Gulf, SW of Hainan Island (South China Sea). (January 2021) - Miluch, Jakub; Osadczuk, Andrzej; Feldens, Peter; Harff, Jan; Maciąg, Łukasz; Chen, Hongjun
Graphical abstract: Highlights: Seismic data and ordinary kriging are used for modeling of paleodelta's geometry. Two deltaic depocenters occur, with sediment thickness up to 80 m. Distributary channels and deltaic clinoforms dip from Hainan Island. Hainan Island is the main source of paleodelta's sediments (65–56 kyr BP). Abstract: High-resolution 2D seismic reflection profiles were examined to explore the stratigraphic architecture of the late Quaternary sediments deposited in the Beibu Gulf (SW off the Hainan Island, South China Sea). Two discontinuities identified in previous research by seismic reflectors R1 (top) and R2 (bottom) allowed to infer the presence of a paleodelta offshore Hainan Island. A detailed analysis of all discontinuities determined the extension of delta body, its thickness and spatial pattern of deltaic clinoforms. Analysis of data obtained by interpretation of seismic records allowed also to depict the relief of lower and upper delta surfaces identified by major erosional discontinuities. The seismic cross-sections provided tools with which to discern all the erosional incisions representing paleo-distributary channels of the delta on both surfaces. In addition, the delta geometry and clinoform dip angles were determined. Analyses have provided information on the direction of sediment transport and sources of deltaic sedimentary material. Distribution of vectors indicating the direction of delta progradation revealed the sediment transport from Hainan Island to be generally southwards to Yinggehai Basin and further towards the shelf edge, thus supporting the hypothesis of Hainan Island as the main source of sediment supply. The vector distribution is unclear in the westernmost part of delta body only, mainly because of an insufficient coverage of this part of the Gulf with seismic tracks and disturbances related to other sediment sources reaching Beibu Gulf in the north, which significantly contributed to the sediment supply.